Cage fish farm act as a source of changes in the fish community of a Neotropical reservoir - Nobile, André Batista [UNESP]; Zanatta, Augusto Seawright; Brandão, Heleno; Zica, E. O.P. [UNESP]; Lima, F. P. [UNESP]; Freitas-Souza, Diogo [UNESP]; Carvalho, Edmir Daniel [UNESP]; Silva, Reinaldo José da [UNESP]; Ramos, Igor Paiva [UNESP] (Elsevier, 2018)
Brazil has shown an increase in cage fish farms activity in reservoirs. However, this activity shows potential to cause several changes in the environment with consequences in the structure of native fish fauna community. Thus, the hypothesis of this work is that three cage fish farms, located in the different areas of Chavantes reservoir, high Paraná basin, have potential to interfere with resident fish communities, modifying their structure. Fish were caught in twelve monthly field samplings around three cage fish farms (FF) (FF1 and FF2 – Dec/06-Nov/07; FF3 – Mar/08-Feb/09) and their respective reference sites (RF) (RF1, RF2 and RF3), using gillnets with 3 to 14 cm between opposite knots. Our data showed that cage fish farms cause increase in fish abundance and biomass around cages. However, Margalef Richness and Shannon-Wiener diversity decreased in these areas. Spatially, fish community around cage fish farms differed from those observed in the reference sites (Permanova two-way: (F = 12.747; p = 0.001)). However, seasonal differences were not observed (F = 1.3732; p = 0.089). This difference was illustrated by NMDS, that showed the formation of two groups, one composed by fish farms and another by reference sites. These differences were mainly influenced by a small group of fish species (Apareiodon affinis, Steindachnerina insculpta (detritivores) and Pimelodus maculatus (generalist) (Simper analysis)) that are able to consume wastes released. We conclude that the cage fish farm act as a driver of alterations in the fish community, increasing the abundance and biomass of a few species which contributes to decrease Richness and Diversity.
Keywords: Aquaculture influence; Diversity; Fish communities; Paranapanema River; Richness